PUTTING PAINTINGS AND PIGMENTS IN PERSPECTIVE:A MULTIDISCIPLINARY STUDY OF ROCK ART FROM THE CENTRAL NARMADA VALLEY, MADHYA PRADESH - Rajesh Poojari (My University, 2025)
Rock art is one of the earliest forms of human expression, offering valuable insights into the lives of ancient communities. In India, rock paintings, found in numerous shelters, span prehistoric to historic times and depict daily life, spiritual beliefs, and artistic practices. However, many rock art sites, particularly in central India, remain understudied, limiting our understanding of these artworks and hindering conservation efforts. This thesis addresses the gap by focusing on the scientific analysis of pigments from the newly discovered rock shelters in the Sehore and Narmadapuram Districts in the Vindhyan and Gondwana ranges. These sites, including Talpura, Mandikhoh, and Chikli-Chandla Kalan, contain over 4,624 individual paintings, 414 cupule marks, and 33 engravings documented across 114 rock art shelters at 15 locations. The study aims to reveal the materials and techniques used by ancient artists, which can offer clues about the age, cultural practices, and environmental conditions of the period. Despite extensive research at Bhimbetka, similar sites in the central Narmada region have been neglected. Modern analytical techniques like X-ray fluorescence (XRF), field-emission scanning electron microscopy (FESEM-EDX), gas chromatography-mass spectrometry (GC-MS), and Raman spectroscopy were applied to analyse the composition of various natural ingredients on the landscape. Comparing these sources with original archaeological pigments in the future can help determine if materials were locally sourced, providing insights into human mobility, land use and social interaction. In addition to the scientific analysis, the thesis emphasises the importance of conserving these fragile paintings and proposing sustainable strategies like non-invasive methods, protective measures, and guidelines for responsible tourism. In conclusion, this study contributes to the understanding of Indian rock art by exploring the materials and methods used by ancient artists in the understudied central Narmada region. It lays the groundwork for future research and provides critical data to support conservation efforts, ensuring that these cultural treasures are preserved for generations to come.
Keywords: PIGMENTS IN PERSPECTIVE